High Pressure Elastic Behavior of Synthetic Mg3Y2(SiO4)3 Garnet up to 9 GPa - Dawei Fan; Maining Ma; Shuyi Wei; Zhiqiang Chen; Hongsen Xie (Advances in Materials Science and Engineering)
The compression behavior of synthetic magnesium- (Mg-) yttrium (Y) garnet Mg3Y2(SiO4)3 has been investigated upto about 8.79 GPa at 300 K using in situ angle-dispersive X-ray diffraction and a diamond anvil cell at the beamline X17C, National Synchrotron Light Source, Brookhaven National Laboratory. No phase transition has been observed within the pressure range investigated. The unit-cell parameters and volume decreased systematically with increasing pressure, and a reliable isothermal bulk modulus (KT0) and its pressure derivative (KT0′) were obtained in this study. The values of zero-pressure volume V0, K0, and K0′ refined with a third-order Birch-Murnaghan equation of state are V0=1727.9±0.2 Å3, KT0=145±3 GPa, and K0′=8.5±0.9. If KT0′ is fixed at 4, KT0 is obtained as 158±2 GPa.